1997
DOI: 10.2307/40285747
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Feedback and Musical Keyboard Performance

Abstract: In an investigation into the role of auditory feedback guidance in musical performance, musically experienced subjects performed on an electronic keyboard under altered feedback conditions that included pitch and timing manipulations, as well as absence of auditory feedback. The results largely replicated the data reported by Gates and Bradshaw (1974): performance in the absence of auditory feedback showed no impairment, whereas performance under delayed auditory feedback showed significant impairment. In an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
6
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 16 publications
12
94
6
1
Order By: Relevance
“…Moreover, Experiment 2 demonstrated disruption when pitch contents of auditory feedback were altered to match past produced events, which contrasts with past research, in which performance was unaffected by manipulations of feedback contents (Finney, 1997;Howell, 1983;Howell & Archer, 1984;Howell & Powell, 1987;Howell et al, 1983). Although other methodological differences may account for discrepancies between the present and past results, Experiment 2 nevertheless provides new evidence that alterations of feedback contents alone can disrupt performance.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Moreover, Experiment 2 demonstrated disruption when pitch contents of auditory feedback were altered to match past produced events, which contrasts with past research, in which performance was unaffected by manipulations of feedback contents (Finney, 1997;Howell, 1983;Howell & Archer, 1984;Howell & Powell, 1987;Howell et al, 1983). Although other methodological differences may account for discrepancies between the present and past results, Experiment 2 nevertheless provides new evidence that alterations of feedback contents alone can disrupt performance.…”
Section: Discussioncontrasting
confidence: 82%
“…The current manipulations differed from those used in past studies (e.g., Finney, 1997;Howell et al, 1983) in that both alterations resulted from calibrations of feedback timing at different levels of a single timing hierarchy via phase and period shifts. The finding of disruption from altered contents when these alterations result from period shifts, as opposed to randomized pitch contents (Finney, 1997), suggests that timing relationships do lie at the root of DAF disruption examined previously (cf. Finney & Warren, 2002;Howell et al, 1983) but that the scope of relevant timing relationships may be broader and more differentiated than originally considered.…”
Section: Links Between Perception and Actionmentioning
confidence: 91%
See 1 more Smart Citation
“…One goal of the present experiments is to confirm that serial shifts disrupt production, in contrast with the negligible disruption that results from randomized pitches or feedback absence (Finney, 1997;Pfordresher, 2003a;Repp, 1999). Experiments 1 and 2 include these conditions in the same session with pianists and nonpianists, respectively.…”
Section: Current Experimentsmentioning
confidence: 92%
“…A qualification of these results is that nondisruptive manipulations of feedback contents result in feedback pitches that are unrelated to planned pitches. For instance, Finney (1997) failed to find disruption of piano performance from a quasi-random mapping between piano keys and pitches. Howell and Archer (1984) likewise demonstrated that DAF disruption of speech was not qualitatively altered when feedback contents (phonemes) were converted to a square wave tone.…”
Section: Effects Of Altered Auditory Feedbackmentioning
confidence: 99%